Analysis of Household Potentials in Fertile-Aged Couplesof Bukit Malintang Family Planning Village, Pasaman Barat - Iskarni, Paus; Surtani, Surtani (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
This study aims to look at the potential of fertile-aged couple’s households and develop strategies to improve the quality of fertile-aged couple’s households in the Family Planning Village of Bukit Malintang. This study combines quantitative and qualitative approaches, with a population of all fertile age couples in the Family Planning Village of Bukit Malintang (90 fertile-aged couple) and all of them are sampled. The results showed that the quality of human resources (HR) of FAC families was relatively low, which was indicated by the relatively low education, health, expertise, and skills of family members. Likewise, with agricultural land ownership, that not all FACs have agricultural land and, also with low land productivity. Ownership of securities, especially land certificates, is used as collateral, mainly used for consumption and not for production. As an effort to improve the welfare of the community (fertile-aged couple’s), several alternatives were proposed, and discussed in a group discussion forum (FGD) with the relevant agencies/institutions of the West Pasaman Regency Government, namely 1). Socialization about genre and family planning 2). Skills training for youth and community members 3). Training/application on agriculture, plantation, fishery, and animal husbandry. 4). Increased yard usage 5). Establishment of Jorong Malintang as a tourist village